Global Multidisciplinary Learning in Construction Education: Lessons from Virtual Collaboration of Building Design Teams - Soetanto, R.; Childs, M.; Poh, P.; Austin, S.; Hao, J. (Civil Engineering Dimension, 2012)
Construction is a multidisciplinary activity in which effective communication between parties is essential for successful construction projects. However, the construction industry has been characterised by fragmentation, which prevents seamless communication. This problem has been further exacerbated by the need to communicate over distance within a time constraint in an increasingly interconnected and globalised construction sector. This has brought a particular challenge to the education sector in preparing the future graduates to work in this context. The paper reports on an on-going Hewlett Packard-sponsored project to implement an innovative learning approach which consists of distanced collaboration between students from different disciplines from two Universities in the UK and Canada. The empirical work involved interviews and questionnaire survey at different stages of the project. The preliminary findings reveal the impact of disciplinary training on the development of effective virtual collaboration, although this has been moderated, to some extent, by their earlier (not so positive) experience during the course of the project. The research provides a material for further reflection and may serve as a useful consideration for future development of a guiding framework for effective training of built environment professionals.